Pembuatan Sistem Penjualan Spare Part Mobil Berbasis Web Pada Usaha “Asen” - Setiawan, Steven; Dewayani, Ery (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2024)
The rapid development of technology nowadays and fairly easy access have resulted in increased use of technology by society. The use of technology can make it easier for people to search for information, both locally and internationally. Technological developments also have an influence in the business sector, where their use can help businesses increase the number of potential buyers who look at the business and the profits of the business. The